2017
DOI: 10.1021/acs.jafc.7b00324
|View full text |Cite
|
Sign up to set email alerts
|

AMPK/α-Ketoglutarate Axis Regulates Intestinal Water and Ion Homeostasis in Young Pigs

Abstract: Water and ion absorption via sensitive aquaporins (AQPs) and ion channels is of critical importance in intestinal health. However, whether α-ketoglutarate (AKG) could improve intestinal water and ion homeostasis in lipopolysaccharide (LPS)-challenged piglets and whether the AMP-activated protein kinase (AMPK) pathway is involved remains largely unknown. This study was conducted to investigate the effect of dietary AKG supplementation on the small intestinal water and ion homeostasis through modulating the AMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 48 publications
4
40
0
Order By: Relevance
“…The present results showed an increase in villus height and a decrease in crypt depth and mucosal thickness in the small intestine of piglets fed the AKG diet. These results were consistent with the pervious study [ 7 ], suggesting that AKG in enterocytes may beneficially regulate the intracellular endogenous amino acid concentrations via TCA cycle [ 23 ] and then influence various signaling pathways [ 16 ], such as the AMP-activated protein kinase (AMPK), nuclear factor kappa B (NF-κB), and mammalian target of rapamycin (mTOR) pathways, thereby improving intestinal morphology.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present results showed an increase in villus height and a decrease in crypt depth and mucosal thickness in the small intestine of piglets fed the AKG diet. These results were consistent with the pervious study [ 7 ], suggesting that AKG in enterocytes may beneficially regulate the intracellular endogenous amino acid concentrations via TCA cycle [ 23 ] and then influence various signaling pathways [ 16 ], such as the AMP-activated protein kinase (AMPK), nuclear factor kappa B (NF-κB), and mammalian target of rapamycin (mTOR) pathways, thereby improving intestinal morphology.…”
Section: Discussionsupporting
confidence: 90%
“…Alpha-ketoglutarate is considered to be a potent therapeutic agent against GIT disorder diseases [ 15 ] and also has potential to implicate as a new feed additive for weaning piglets [ 16 ]. Many reports have suggested that maternal and neonatal administration of AKG could improve the growth performance of piglets [ 7 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, a significant (p<0.01) increase in the mRNA expression level of the TORC2 gene in the small intestine is in line with the findings of Liuqin et al, 2017. They further concluded that the AMP-activated protein kinase (AMPK) pathway, which is regulated by the TORC2 gene, is mainly responsible for water and ionic homeostasis in the small intestine in pigs [59]. After the small intestine, we found a significant increase in the TORC2 gene mRNA relative expression in muscle and fat tissue.…”
Section: Discussionmentioning
confidence: 73%
“…The improvement in daily body weight gain and diarrhea score may be a result of the beneficial effects of serine for maintaining gut health [12].…”
Section: Discussionmentioning
confidence: 99%